Comparison of variable-flux PMSG for extended speed-range based on magnet arc-length to pole-pitch ratio - Gupta S.K.; Srivastava R.K. (My University, 2025)
This paper discusses voltage regulation (VR) of PMSG for a wind energy conversion system (WECS) under varying wind conditions. Mechanical flux-variation technique (MFV) has been used for VR of a kaman-type dual-stator axial-flux PMSG at above rated rotor/wind speed extending the speed range of generator. An experimental test-bed has been set up to implement MFV in the generator and subsequently, the implications of proposed technique on the performance of generator has been analyzed. Total harmonic injected in generator output due to proposed technique has been calculated by FFT analysis and compared for two types namely, sinusoidal and trapezoidal back-emf characteristics. © 2017 IEEE.